A prognostic model based on prognosis-related ferroptosis genes for patients with acute myeloid leukemia - Wu, Feima; Xu, Guosheng; Li, Guangchao; Yin, Zhao; Shen, Huijuan; Ye, Kaiheng; Zhu, Yangmin; Zhang, Qing; Ou, Ruiming; Liu, Shuang (Frontiers in Molecular Biosciences, 2023)
Background: Acute myeloid leukemia (AML) is a heterogeneous disorder with an unpredictable prognosis. Ferroptosis, the iron-dependent cell death program, could serve as an alternative for overcoming drug resistance. However, its effect on AML remains largely unclear.: We collected RNA sequencing data and relevant clinical information of AML patients from The Cancer Genome Atlas to construct a prognosis prediction model. Risk score was calculated with eight prognosis-related ferroptosis genes (PRFGs) discovered through univariate analysis and Least Absolute Shrinkage and Selection Operator (LASSO) Cox regression. A nomogram was constructed by incorporating LASSO risk score, age, and cytogenetic risk based on univariate/multivariate Cox regression.Results: Of the 33 AML PRFGs identified from the TCGA-derived dataset, 8 genes were used to construct a gene signature to predict AML prognosis. Principal component analysis and heatmap showed significant differences between the low and high risk score groups. Next, LASSO risk score, age, and cytogenetic risk were incorporated into the nomogram to predict the overall survival (OS) of AML patients.According to survival analysis, patients with a low risk score had markedly increased OS as compared to those with a high risk score. Based on the results of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes, the differences between the two risk groups showed a close relationship with immune-related pathways and membrane transportation. The analysis of tumor-infiltrating immune cells and immune checkpoints revealed that the immunosuppressive tumor microenvironment possibly facilitated different prognostic outcomes between the two groups. Gene expression analyses showed that the mRNA expression levels of PARP1 and PARP3 (PARPs) were closely related to the different clinical subgroups and the analyzed OS in AML patients. Finally, the PARP inhibitor talazoparib and the ferroptosis inducer erastin exerted a synergistic anti-proliferative effect on AML cells.We constructed a nomogram by incorporating PRFGs, and the constructed nomogram showed a good performance in AML patient stratification and prognosis prediction. The combination of PARP inhibitors with ferroptosis inducers could be a novel treatment strategy for treating AML patients.